High temperature lead free solder - Song, Glenn Qi Xuan (2017)
Due to its availability and affordability, Zinc-Aluminium (Zn-Al) based alloys have been studied extensively as a possible alternative for lead based solders. Furthermore, amongst the Zn based systems, Zn-Al possesses good thermal and mechanical properties. At present, plenty of studies have been done mainly on the interconnecting properties and process optimization for solder reflow. In this study, we will explore how the addition of different elements such as Magnesium (Mg) and Germanium (Ge) will affect the thermo-mechanical properties. Furthermore, the effects of phase transformation on the properties will be studied as well. Four different Zn-Al alloys – Zn-6Al (ZA), ZN-4.3Al-4.2Mg (ZAM), Zn-8.4Al-8.4Ge (ZAG) and Zn-6.5Al-0.8Mg-1.0Ge (ZAMG) are prepared in an induction furnace under an inert Ar gas atmosphere and cast into cylindrical rod. Microstructures, thermal properties, thermal expansion, electrical resistivity and thermal conductivity measurements are analysed and compared. It is found that the addition of Mg or Ge will decrease the eutectic melting point. As for the coefficient of thermal expansion (CTE), Scanning Electron Microscopy (SEM) and X-ray Fluorescence (XRF) analyses have revealed that Zinc rich hexagonal closed packed (hcp) phase is responsible for the CTE differences. Increasing amount of Al content and decreasing amount of Mg or Ge content would result in the decrease inelectrical resistivity and an increase in thermal conductivity.